Controle ótimo e comparação das geometrias dos mancais magnéticos - Corrêa, Yago Pessanha (2020)
Active Magnetic Bearings (AMB) are devices that support a shaft, owning the advantage of having no contact with any rotating parts, thus eliminating wear and the need of lubrication. Intrinsically, these equipments are unstable and, therefore, a control strategy is necessary in order to stabilize the system. One of the most widely used state-space feedback methods is the Linear Quadratic Regulator (LQR). This Dissertation aims to simulate and compare the geometries of the eight, four and three-pole AMB with the centralized, decentralized and two-parameter decentralized LQR control strategies. After deducting the reluctance force equations and the system dynamics equations for each of the geometries, several simulations are performed. The results are conclusive and indicate the preference to use the two-parameter decentralized controller, due to the shorter stabilization time and the control variables decoupling, among other factors.